Knowledge management system architecture for the industry cluster - P. Sureephong (2018)
Since the concept of the industry cluster was popularized by Porter in 1990, many countries try to improve the competitiveness through industry sector. Not only companies who take part in the cluster but also academic institutes, government agencies, associations, and supportive industries. The more actors involved in the cluster the more knowledge were distributed among the member of cluster. Although, many literatures about cluster explained how knowledge is important for the cluster development But, there is no specific knowledge management methodology or system for the cluster. This study is concerned about knowledge exchange in the cluster by using knowledge engineering methodology to analyze, model and design Knowledge Management System (KMS). At the end of this study, KMS will be studied the possibilities of implementing in the handicraft cluster in Thailand as our case study. This paper present methodology and primary result from knowledge engineering. Then the KMS architecture was proposed as the result of the preliminary study in this paper. © 2007 IEEE.